A systematic review and meta-analysis of discrepancies between logged and self-reported digital media use - Parry, Douglas A.; Davidson, Brittany I.; Sewall, Craig J. R.; Fisher, Jacob T.; Mieczkowski, Hannah; Quintana, Daniel S. (Nature human behaviour, 2021)
There is widespread public and academic interest in understanding the uses and effects of digital media. Scholars primarily use self-report measures of the quantity or duration of media use as proxies for more objective measures, but the validity of these self-reports remains unclear. Advancements in data collection techniques have produced a collection of studies indexing both self-reported and log-based measures. To assess the alignment between these measures, we conducted a pre-registered meta-analysis of this research. Based on 106 effect sizes, we found that self-reported media use correlates only moderately with logged measurements, that self-reports were rarely an accurate reflection of logged media use and that measures of problematic media use show an even weaker association with usage logs. These findings raise concerns about the validity of findings relying solely on self-reported measures of media use. In a pre-registered meta-analysis, Parry et al. find that, when self-reported media use is compared with digital logs of media use, subjective judgements are often inaccurate. This suggests caution when self-reports are used to test associations between media use and other outcomes.